Tensiones jurídicas entre lo público y privado en los conflictos por jubilación patronal en las federaciones deportivas provinciales del Ecuador - Lasso Montenegro, Carla Dennisse (2023)
In Ecuador, employer-funded retirement, known as "jubilación patronal," grants individuals who've served in a single company for a minimum of twenty years a lifelong pension. Introduced in 1938, this form of retirement served as an alternative for those ineligible for benefits from the then newly established Social Security Fund. Ecuador’s Labor Code mandates this employer obligation for workers with twenty-five years of continuous or interrupted service. On another note, the 2010 Sports, Physical Education, and Recreation Law characterizes provincial sports federations as planners and coordinators of provincial sports activities. These federations, though private entities, receive public funding upon the Ministry of Sport's approval of their annual operational plan. This places them under the 2008 Ecuadorian Constitution's mandate for transparency, accountability, and public control. Tensions arise when the Ministry of Sport, since 2019, prohibits the inclusion of retirees' payments in the state budget. This leaves many non-profit sports federations unable to fund these obligations, leading to conflicts and violations of the employer-funded retirement payment. The Pichincha Sports Federation retirees, facing this non-payment issue, sought legal protection against potential constitutional rights breaches, emphasizing the state's responsibility in assuring rights protection. The ruling accentuated the state's responsibility in these situations, setting a precedence for future cases. Moreover, these sports federations have a critical role in adapting and perfecting methods to ensure sports remain a potent tool for sustainable development in Ecuador, going beyond mere entertainment or competition to contribute significantly to a better future.